Physicians' Perspective On Preventing Stress Peptic Ulcer Disease At King Abdullah Hospital In Bisha City, Saudi Arabia (The Review of Diabetic Studies, 2025)
Objective: This study was focused on determining Physicians' perspectives on Stress-Peptic Ulcer Disease prevention and assessing their understanding of SUP guidelines in KSA.Methods: This descriptive cross-sectional study assessed Physician's knowledge about Stress Peptic Ulcer Disease prevention at King Abdullah Hospital (KAH). The study involved physicians and interns at KAH in Bisha City. The data was collected using an electronic questionnaire through text messages or phone calls. Both data entry and statistical analyses were performed using SPSS. The appropriate statistical tests were used and considered statistically significant at P